Behavioural flexibility in spider mites: oviposition site shifts based on past and present stimuli from conspecifics and predators. Issue 7 (19th July 2017) - Murase, Aoi; Fujita, Kazuo; Yano, Shuichi
Abstract : Predator-experienced individuals often change their predation avoidance response when they re-encounter the same predators or their cues. Recent reports show that behavioural change sometimes occurs even before the re-encounter. To function as an adaptive strategy in the wild, such prospective experience-induced behaviour should change flexibly in response to changing situations. We assessed flexibility of experience-induced oviposition site shift in two closely related species of spider mites, Tetranychus kanzawai and T. urticae, from the viewpoint of reducing future predation risk on their eggs. We found that: (i) individuals of T. kanzawai shifted oviposition site depending on the presence of conspecific eggs; (ii) after experiencing predation threat T. kanzawai females shifted oviposition site even in the absence of any current predation threat; (iii) this experience-induced shift of oviposition site was weakened in the presence of conspecific males; and (iv) experience-induced behaviour was retained for a shorter period in T. urticae than in T. kanzawai, possibly because the demand for learning may differ with regard to biological conditions encountered in the wild.